Adaptation and Infection of Mouse Bone Marrow (JLS-V9) Cells in Suspension Culture for Production of Rauscher Leukemia Virus - Hodge, Howard M. (1974)
JLS-V9 mouse bone marrow cells were readily adapted to suspension culture, chronically infected with Rauscher leukemia virus (RLV), and subsequently grown in 7.5- and 14-liter New Brunswick fermentors. The suspension-type cell system can be modified to produce virus with clearly defined properties, such as high ribonucleic acid-dependent deoxyribonucleic acid polymerase (RDDP) activity, high particle count, and high infectious particle count. Biological and biophysical properties of suspension-produced RLV were not affected by concentration and purification employing continuous-flow and rate-zonal centrifugation procedures. The RDDP assay was standardized and showed a linear incorporation of (3)H-thymidine 5′-monophosphate ((3)H-TMP) up to 30 min. Further characterization indicated that a high percentage of (3)H-TMP incorporation was due to RDDP.